Examining the Impact of Economic Development Indicators on Reducing the Adverse Environmental Effects of Corporate Activities - Kamrani, Hosein (Business, Marketing, and Finance Open, 2024)
Environmental issues facing society have become so extensive that governments alone cannot effectively address them. Taxation and regulatory measures to limit negative impacts, as well as incentive policies for activities with positive effects, are among the strategies adopted by governments in this regard. The purpose of this study is to examine the impact of economic development indicators on reducing the adverse environmental effects of corporate activities. The statistical population of the study includes senior executives, middle managers within relevant organizational domains, university professors, and informed economic actors. Given its objectives, this research falls under the category of applied studies. In terms of its methodological approach, it is classified as a descriptive and survey-based exploratory study conducted in both qualitative and quantitative sections. The results indicate that in the economic growth model, strategies influence outcomes, with a path coefficient of 0.841. The t-statistic for this relationship was reported as significant at a 95% confidence level (P-Value ≤ 0.05). Accordingly, the null hypothesis of the study is rejected, and the alternative hypothesis is confirmed, meaning that strategies have a positive and significant impact on outcomes. Therefore, based on the study's findings, economic development indicators in the environmental domain assist managers in the proper implementation and efficient management of financial and physical resources, identifying cost-reduction opportunities, and making better decisions. Additionally, from an external perspective, this technique provides valuable information to stakeholders, such as shareholders, creditors, analysts, and environmental organizations, in both financial and environmental contexts.